Automating algorithm selection: Checking for matrix properties that can simplify computations. (September 2019) - Eberly, Wayne
Abstract: Initial findings in a study of the automatic selection of algorithms for matrix computations are reported. These include the presentation and analysis of algorithms for the detection and certification of matrix properties allowing the reliable use of a variety of special-purpose algorithms for sparse and structured matrix computations.